PROPOSING PROMOTIONAL STRATEGY FOR POULTRY EQUIPMENT PRODUCT CASE STUDY: PT MEDION – BANDUNG INDONESIA - Kannida Puspa Shubhi; Atik Aprianingsih (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research aims to propose a better promotional strategy for poultry equipment products at Medion, Bandung, Indonesia. This research uses a case study approach to explore why the sales of poultry equipment product have been declining for 5 years. The research focuses on how to define the current positioning of poultry equipment products and how to communicate the product’s value more clearly to customers in a B2B (business-to-business) marketing context. Data were collected using surveys and interview. The survey involved farm, distributor, and partnership customers who use poultry equipment products. The methods used in the analysis marketing mix and perceptual mapping. The result shows that mostly customers see the company’s products have high-quality. Even so the sales declining shows that the product is not promoted well. Many customers prefer to buy the products through online shop platforms, good price products, and good after-sales service. Based on the analysis, this research suggests promotional strategy such as value education campaign, boost the online shop platforms, reach small farmers, and promote the practical innovation.